A Fluid-structure Interaction Analysis of the Spring-Loaded Pressure Safety Valve during Popping Off. (2015) - Song, X.G.; Wang, L.T.; Park, Y.C.; Sun, W.
Abstract: Many industrial engineering problems require fluid-structure interaction (FSI) analysis and dynamics analysis to improve functionality or operational performance. One such problem is the popping off of pressure safety valve (PSV) widely used in pressure vessels and pipes. Popping off of a spring-loaded pressure safety valve (PSV) is crucial to prevent the pressure vessel or pipe from overpressure. It's difficult to observe the dynamics of the valve disc as well as the flow characteristics through the small chamber between the valve disc and valve seat over such a remarkable short period in the past. To address this issue, a transient computational fluid dynamics (CFD) model with moving grid technique has been presented in this work. Fine structure grid has been generated over the whole flow domain to ensure that the valve disc can move freely and continuously without negative volume problem. Two types of time-dependent overpressure are given to simulate the popping of the PSV under different overpressure conditions. Response parameters such as the displacement of the disc, fluid force on the disc and the blowdown value are monitored to see their influence on the popping of the valve. The results are helpful to improve the popping action of the valve in design stage, and demonstrate the availability and efficiency of using transient CFD simulation in the popping analysis of spring-loaded PSV.